ANALISIS IMPLEMENTASI AKAD ISTISHNA PEMBIAYAAN RUMAH (STUDI KASUS DEVELOPER PROPERTY SYARIAH BOGOR) - Hidayah, Muhammad Rizki; Nawawi, Kholil; Arif, Suyud (Universitas Muhammadiyah Prof DR HAMKA, 2018)
This study aims to determine the implementation of istishna in application home financing Developer Property Sharia Bogor. This research using descriptive qualitative research to according This type of research was descriptive qualitative research with illustrative for solving the problem. The result of this research is Akad or transaction that applied by Developer Property Sharia using istishna without interest, without penalty, unguaranteed of goods belong to a buyer, and price credit is fixed until paid off.